La regularización tributaria en el derecho penal peruano: fundamentos, presupuestos y aplicación - Pariona Arana, Raúl (Pontificia Universidad Católica del Perú, 2025)
The article examines tax regularization in the Peruvian legal system, focusing particularly on the foundations that legitimize it, the requirements for its application, and the challenges faced in its practical implementation. The significance of this legal institution lies in its capacity to exempt the perpetrator of a tax crime from criminal prosecution, provided they inform the authority of their unlawful act and pay the full amount of the tax debt generated by the offense, plus interest and the fine. The criminal policy considerations that justify waiving criminal prosecution prioritize the effectiveness of tax collection and acknowledge the achievement of criminal law objectives through this mechanism. The article is structured in five sections comprising: i) an approach to the institution of tax regularization, ii) the foundations of legitimation, iii) the discussion of its legal nature, iv) its requirements, and v) the challenges of practical application in Peru.

El artículo aborda la regularización tributaria en el ordenamiento jurídico peruano, atendiendo en especial a los fundamentos que la legitiman, los presupuestos de aplicación y los problemas que enfrenta su aplicación práctica. La relevancia de esta institución jurídica radica en que posibilita que el autor de un delito tributario se libre de la acción penal si informa a la autoridad de su ilícito y paga el íntegro de la deuda tributaria originada por el delito, más los intereses y la correspondiente multa. Las razones de política criminal que justifican la renuncia a la persecución penal priorizan la efectivización de la recaudación tributaria y la consideración del logro de los fines del Derecho penal por esta vía. El artículo se estructura en cinco apartados que comprenden: i) la aproximación a la institución de la regularización tributaria; ii) los fundamentos de legitimación; iii) la discusión sobre su naturaleza jurídica; iv) sus presupuestos; y v) los problemas de su aplicación práctica en el Perú.
Tax regularization in criminal law: foundations, requirements and application
Keywords: Criminal Law; Tax crime; Tax Code; Tax regularization; Punishment; Criminal policy; Derecho penal; Delito tributario; Código Tributario; Regularización tributaria; Punibilidad; Política criminal; https://purl.org/pe-repo/ocde/ford#5.05.00